Di-Genic Inheritance in Genodermatoses: Insights from Two Consanguineous Cases in a Reference Lebanese Center within the Middle East and North Africa (MENA) Region - Kadhi, Ayat; Hamie, Lamiaa; Eid, Edward; Nemer, Georges; Kurban, Mazen (Dermatology Practical & Conceptual, 2025)
Introduction: Genodermatoses refer to a group of heterogenous rare genetic diseases with cutaneous expression. Several genodermatoses present with multisystem involvement that can range from mild to life-threatening conditions leading to increased morbidity and mortality. Objective: Given the paucity in the literature in the field of genodermatoses especially in the Middle East and North Africa (MENA) region and building up on the first established genodermatoses database based in Lebanon, this article aimed to decipher the genetic basis of 2 different types of skin-inherited diseases (androgenic alopecia and vitiligo). Methods: Herein, we propose the first di-genic model of inheritance which could be responsible for these 2 diseases, using Whole Exome Sequencing (WES) and GEO datasets. Results: We identified 2 gene variants FOXC1(p.His484Tyr) and SMARCD1 (p.Arg351Cys) responsible for androgenic alopecia and HPS1(p.Ser566Ter) and ITK (p.Pro521Leu) responsible for vitiligo. Further analysis using GEO datasets, confirmed the connectivity between the genes involved in each each disease. Conclusion: This study identified novel candidate disease genes and inheritance model that could explain the underlying phenotypes that could open the doors for a better-guided genomic approach for personalized treatment and early diagnosis.